Acid-base balance of the fetus during normal labor - Bautista Montalvo, Elsa (2015)
30 fetuses, classified as normal according to criteria related to the mother, fetus, childbirth and newborn was selected. By the method of Astrup-Siggaard-Andersen, evaluation of acid-base balance in capillary blood samples obtained from the fetal presentation, using the technique of Saling they were made.